Ethanol production from biomass by repetitive solid-state fed-batch fermentation with continuous recovery of ethanol - Moukamnerd,C. (Springer Verlag, 2015)
To save cost and input energy for bioethanol production, a consolidated continuous solid-state fermentation system composed of a rotating drum reactor, a humidifier, and a condenser was developed. Biomass, saccharifying enzymes, yeast, and a minimum amount of water are introduced into the system. Ethanol produced by simultaneous saccharification and fermentation is continuously recovered as vapor from the headspace of the reactor, while the humidifier compensates for the water loss. From raw corn starch as a biomass model, 95∈±∈3, 226∈±∈9, 458∈±∈26, and 509∈±∈64 g∈l-1 of ethanol solutions were recovered continuously when the ethanol content in reactor was controlled at 10-20, 30-50, 50-70 and 75-85 g∈kg-mixture-1, respectively. The residue showed a lesser volume and higher solid content than that obtained by conventional liquid fermentation. The cost and energy for intensive waste water treatment are decreased, and the continuous fermentation enabled the sustainability of enzyme activity and yeast in the system. © 2010 Springer-Verlag.